CXCL5 is associated with the increased risk of coronary artery disease. Issue 7 (November 2015) - Wang, Xiao-Zeng; Liu, Li-Wen; Du, Xiao-Mo; Gu, Ruo-Xi; Sun, Zhi-Jun
Abstract : Objective: To investigate the relevant expression of CXCL5 and CXCR2 in human atherosclerotic coronary artery and to study the association between the CXCL5 variant and coronary artery disease (CAD) in a Chinese Han population. Materials and methods: CXCL5 and CXCR2 expression in human coronary arteries was detected by immunohistochemical staining and western blotting analysis. The association between the CXCL5 variant and CAD was determined in a community-based sample by PCR-direct sequence analysis in a Chinese Han population. Finally, plasma CXCL5 levels were measured in a case–control study of CAD patients. Results: We found that CXCL5 and CXCR2 expressions were higher in atherosclerotic coronary arteries plaque than in the normal coronary arteries. CXCL5 and CXCR2 expression levels increased in line with coronary artery lesion stages. A functional nonsynonymous −156 G/C in the CXCL5 promoter region was associated with CAD and plasma CXCL5 levels were significantly increased in CAD patients compared with control subjects (3891.21±1403.08 vs. 2812.39±840.62 pg/ml, P <0.05). Individuals with the CXCL5 promoter −156 G/C variant C/C and G/C carriers had higher plasma CXCL5 levels than those with the G/G genotype carriers in both CAD patients and control participants. Conclusion: CXCL5 and CXCR2 are enriched in human atherosclerotic coronary artery. Our findings show that the CXCL5 variant might be a genetic risk factor for the susceptibility of CAD and the CXCL5 promoter −156 G/C C allele might be an independent predictor for CAD. CXCL5 may be a useful molecular marker and a possible target for the treatment of CAD.